ECHINODERM SKELETAL PRESERVATION: CALCITE-ARAGONITE SEAS AND THE MG/CA RATIO OF PHANEROZOIC OCEANS - Dickson J.A.D. (My University, 2004)
The alternation between abiotic calcite and aragonite precipitation in shallow seawater and the oscillation of seawater Mg/Ca ratio throughout the Phanerozoic are both popular hypotheses. Echinoderms with well-preserved stereom provide new empirical evidence that supports both these hypotheses. Analyses are reported from 29 specimens, Cambrian to Eocene age, containing ossicles preserved either as Mg calcite, 3.3 to similar to8 mole% MgCO3, or as mixed calcite and dolomite, similar to5 to 12.5 mole% MgCO3. Echinoderms with high mole% MgCO3, occur in the Early Cambrian and late Carboniferous to Triassic; low values come from the Silurian and Jurassic to Cretaceous. The average composition of echinoderms with preserved stereom does not fall below 3.5 mol% MgCO3 during the Phanerozoic and reaches its highest mean value of 16.0 mol% MgCO3 today. An empirical partition coefficient of 0.03182 for modern tropical echinoids is used to indicate the Mg/Ca ratio of ancient seawater from the Mg/Ca ratio of fossil stereom; some assumptions are involved and a likely error is calculated from the Mg2+ variation of modern echinoids. High mean seawater Mg/Ca ratios are calculated for early Cambrian (3.3) and the late Carboniferous to Triassic (2.3) but never reached today's value of 5.2; low Mg/Ca ratios (1.1) are indicated from Jurassic to Cretaceous echinoderms. The 29 echinoderm samples plot close to first-order Mg/Ca seawater oscillations derived from geochemical models and Mg/Ca ratios determined from fluid inclusions, but considerable discrepancies exist when shorter (10(6) Myr) time intervals are considered. Further data and improved understanding of Mg partitioning is required before accurate secular variation in the Mg/Ca of seawater can be determined from echinoderms. However, they are an underused resource in this context and provide an excellent seawater archive.